A Comparative View of "A Third Labour Dispute Management System" of China with Ethiopia: Some Cases as Evidence and Recent Labour Issues of both Jurisdictions - Dessie Tilahun Ayalew (Technium Social Sciences Journal, 2020)
The history and political economy transition of China and Ethiopia are quite similar in many aspects. Long history, socialist transition, and legal reform can be mentioned as points of comparison. Among the legal reforms of the two countries, the labor law reform and the determination of working forces (labour forces) was quite critical in both countries that stayed in socialist sentiments though the Chinese model is still "socialism with Chinese characteristics." The opening up and reform of the two countries, the 1978 reform and opening of China and the 1991 market economy declaration of Ethiopia paved the way to shape the labour law legal regime of the two countries. Especially, the labour dispute management system of the two countries shares unique commonalities. The involvement of arbitration in labour dispute system in each jurisdiction has its own unique features. Thus, the paper tried to compare the labour law legal regime, the labour law dispute management system, and the current labour issues of China and Ethiopia. The findings indicate that there are many similarities that the two countries share and can benefit from mutual experience sharing. But, in cases of China, the issues of collective bargaining and labour union-related rights are at their early stage of development. And the treatment of migrant workers and the law, as well as the practice of triangular relationship among the worker, the forwarding unit and receiving unit is very crucial that experience can be taken from it.